Investigation of Manufacture Tolerances on Torque Pulsation Profile of Interior Permanent Magnet Motor with Third Harmonic Injected Sinusoidal Rotor Iron Pole - Ahlam Luaibi Shuraiji; Kassim Rasheed Hameed; Salam Waley Shneen (Universitas Ahmad Dahlan, 2026)
Torque ripple is a significant undesirable aspect of permanent magnet (PM) machine. It is mainly contributed by cogging torque, which is inherit feature of the PM machine. Interior permanent magnet (IPM) motor with a sinusoidal + third-order harmonic injected rotor pole shape has been introduced as one of the most efficient rotor pole arc iron shape techniques to minimize the cogging torque. Such method showed a reduction in the cogging torque compared to the traditional designs. Generally, imperfections in the manufacturing process can exacerbate cogging torque and, by extension, torque ripple. This research assesses how manufacturing tolerances influence the torque ripple of the IPM motor having sinusoidal + third order harmonic rotor pole shape. The investigation has been carried out using two-dimension finite element analysis(2D-FEA) method, ANSOFT MAXWELL program. Different models of the IPMs with sinusoidal + third order harmonic rotor pole shape have been made to simulate healthy, eccentricity and PM diversity cases. According to the simulation results, it has been found that PM diversity leads to introduce additional harmonics in the cogging torque waveforms, i.e., in addition to the fundamental harmonic, which is the 60th harmonic orders, the 12th harmonic and its multiples harmonic orders were presented, consequently resulting in increasing the torque ripple. Moreover, the obtained results have shown that the static eccentricity has more negative effect on the torque ripple compared to the dynamic counterpart, i.e. the torque ripple of the static eccentricity is about 20% higher than that of the dynamic counterpart.